Rekam Jejak Perjuangan Ki Ageng Basyariyah di Madiun Selatan 1710-1811 - Melani, Zuanti Fitria Melani (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
This article is about the figure of Ki Ageng Basyariyah or Raden Mas Bagus Harun as the village founder and the bearer of the Syattariyah Tariqa in Sewulan village, Dagangan sub-district, Madiun regency. The purpose of this research is to reveal the role of Ki Ageng Basyariyah in the establishment and deployment of the Syattariyah Tariqa and its teachings in Sewulan village. In this study, the researcher uses a historical research method using a qualitative approach. There are several findings in this research. First, the biography and genealogy of Ki Ageng Basyariyah are still continued until Panembahan Senopati to Maulana Malik Ibrahim. Second, the role of Ki Ageng Basyariyah to build Sewulan village after helping Sunan Pakubuwono II in Geger Pecinan. Third, the Syattariyah Tariqa brought by Ki Ageng Basyariyah in Sewulan was obtained from his teacher, Kiai Ageng Muhammad Besari.